2022
DOI: 10.1029/2022gl098522
|View full text |Cite
|
Sign up to set email alerts
|

Observed Equatorward Propagation and Chimney Effect of Near‐Inertial Waves in the Midlatitude Ocean

Abstract: The propagation characteristics of near‐inertial waves (NIWs) and how mesoscale and submesoscale processes affect the waves' vertical penetration are investigated using observations from a mooring array located in the northeast Atlantic. The year‐long observations show that near‐inertial motions are mainly generated by local wind forcing, and that they radiate equatorward and downward following several strong wind events (wind stress ≳0.5 N m−2). Observational estimates of horizontal group speed typically exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 60 publications
3
13
0
Order By: Relevance
“…It is clear from Figure 9a that the observed strong turbulence was located below the strongest stratification at depths of 30-40 m. Instead, S 2 peaked right in (instead of below) the strongest stratification layer (∼23 m depth, Figure 9b). Previous studies have also documented that the near-inertial shear was most likely quickly dissipated at the base of the mixed layer (e.g., Yu et al, 2022). There was a secondary large shear layer lying below the isopycnal of 25 kg m −3 at depth of ∼40 m during the first 8 hr.…”
Section: Shear Instabilitymentioning
confidence: 73%
See 1 more Smart Citation
“…It is clear from Figure 9a that the observed strong turbulence was located below the strongest stratification at depths of 30-40 m. Instead, S 2 peaked right in (instead of below) the strongest stratification layer (∼23 m depth, Figure 9b). Previous studies have also documented that the near-inertial shear was most likely quickly dissipated at the base of the mixed layer (e.g., Yu et al, 2022). There was a secondary large shear layer lying below the isopycnal of 25 kg m −3 at depth of ∼40 m during the first 8 hr.…”
Section: Shear Instabilitymentioning
confidence: 73%
“…H08 was characterized by moderate wind speed (∼8 m s −1 ) during the observation period, the wind generally showed a quite intermittent feature during the 1-month period since August 13. The wind energy flux into near-inertial motions can be dominated by such intermittent events with duration of several days (Yu et al, 2022), resulting in prevailing near-inertial responses in the mixed layer (Figure 7b).…”
Section: Near-inertial Pycnocline Shearmentioning
confidence: 99%
“…Four casts within 24 hours are sufficient to resolve the amplitude by 0.05 ms −1 and the phase by π/12 = 1 hour. As demonstrated by mooring observation (Yu et al, 2022), the internal waves below mixed layers are observed in response to wind events. The wave propagates at a speed of 50 to 80 m/day (Yu et al, 2022).…”
Section: Discussionmentioning
confidence: 87%
“…As demonstrated by mooring observation (Yu et al, 2022), the internal waves below mixed layers are observed in response to wind events. The wave propagates at a speed of 50 to 80 m/day (Yu et al, 2022). It is quite plausible to observe by ship these near-inertial waves at around 500 m depth after 6 to 10 days after a storm.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation